Evaluation of groundwater quality in the Bancários region in João Pessoa - PB (Research, Society and Development, 2021)
Groundwater is the most sought-after alternative sources to supply the demand for human supply, as they generally present a good quality, due to the soil functioning as a natural filter for its purification. In this sense, this study aimed to evaluate the quality of groundwater in the vicinity of Bancários neighborhood in João Pessoa - PB, as compared with the Portaria de Consolidação nº 05/2017 from Brazilian Ministério da Saúde on water potability standards, as well as in Resolution No. 396/2008 from CONAMA that deals with the classification and environmental guidelines for the framing of groundwater according to its preponderant uses. The research used information from 26 physico-chemical and bacteriological analyses of water provided by five residential condominiums, covering the period from 2012 to 2018. The results are presented through graphs for the evaluated physico-chemical parameters (chloride, acidity, pH, color, total hardness, turbidity, total dissolved solids), while the analysis of variance was performed by the GT-2 method, with significance level of 5%. The research also addressed bacteriological analyses of these wells. The results showed that there is no significant difference from the statistical point of view between the well means, and the samples are within the standards established by the above mentioned legislations, except for some samples for the parameter pH.